The Influence of Work Environment and Organizational Culture on Employee Performance at UPTD. Habibola Health Center - Yohanes Amolius; Maria Silvana Mariabel Carcia; Vinsensius Ama Muda (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to: (1) determine the description of employee performance, work environment and organizational culture; (2) analyze the influence of the work environment and work experience on employee performance both partially and simultaneously. The population in this study were employees at UPTD. Habibola Community Health Center, numbering 30 people. Because the population is limited, this research was conducted by census or saturated sampling. Data was collected through questionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression. Hypothesis testing is carried out through the F test and t test. The results of the descriptive analysis show that the employee performance variables, work environment and organizational culture are categorized as good. The statistical results of the t test show that partially the Work Environment and Organizational Culture variables have a positive and significant effect on employee performance. The statistical results of the F test show that simultaneously the Work Environment and Organizational Culture variables have a significant effect on employee performance. The results of the determination analysis show that the two independent variables in this study are able to explain variations in the ups and downs of employee performance at UPTD. Habibola Community Health Center was 31.5%.